IMPLEMENTASI PROGRAM DIGITALISASI SUPERVISI AKADEMIK KEPALA SEKOLAH DALAM MUTU KINERJA GURU DI SMP MUHAMMADIYAH AL MUJAHIDIN GUNUGKIDUL - Nugroho, Eko Priyo Agus; Hidayati, Dian (Academy of Education Journal, 2023)
Digitalization program of academic supervision by the school principal is able to improve the quality of teachers' performance. This research aims to determine the implementation of the digitalization program of academic supervision by the school principal on the quality of teachers' performance at SMP Muhammadiyah Al Mujahidin Gunungkidul. The research method used is descriptive with a qualitative approach, and the research subject is the school principal. Data collection techniques involve conducting unstructured interviews and documentation. The results of this study conclude that the digitalization program of academic supervision by the school principal through the use of the Academic Supervision Application (ASA) greatly assists the principal's tasks. The school principal can effectively and efficiently conduct supervision and provide direct feedback to teachers. Therefore, the quality of teachers' performance can be continuously improved